IBM QRadar Version 7.3 : planning and installation guide - Carabaguiaz, Elias (IBM redbooks., 2018)
Helping you understand the features and benefits, this IBM Redbooks publication provides information about implementing IBM QRadar for Security Intelligence and Event Monitoring (SIEM) and protecting an organization's networks through a sophisticated technology. --